2015
DOI: 10.1080/1745039x.2015.1093873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a plant product consisting of green tea and curcuma extract on milk production and the expression of hepatic genes involved in endoplasmic stress response and inflammation in dairy cows

Abstract: During the periparturient phase, cows are typically in an inflammation-like condition, and it has been proposed that inflammation associated with the induction of stress of the endoplasmic reticulum (ER) in the liver contributes to the development of fatty liver syndrome and ketosis. In the present study, the hypothesis that supplementation of dairy cows with a plant product consisting of green tea (95%) and curcuma extract (5%) rich in polyphenols attenuates inflammation and ER stress in the liver during earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 38 publications
10
72
1
1
Order By: Relevance
“…In a recent study of our group, supplementation of polyphenol‐rich grape seed and grape marc meal extract at a dietary level of 1% also did not improve the plasma antioxidant status of dairy cows (as assessed by determination of α‐tocopherol, β‐carotene, TBARS and total antioxidative capacity in plasma) (Gessner et al., ). In another study, feeding a polyphenol‐rich plant product consisting of green tea and curcuma extract also did not exert antioxidant effects in dairy cows (Winkler et al., ). Collectively, it can be stated that, like in most studies with monogastric animals, the antioxidant status of dairy cattle is less influenced by supplementation of feed rations with polyphenols from plant sources.…”
Section: Effects Of Polyphenols On Oxidative Stress and Inflammation mentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study of our group, supplementation of polyphenol‐rich grape seed and grape marc meal extract at a dietary level of 1% also did not improve the plasma antioxidant status of dairy cows (as assessed by determination of α‐tocopherol, β‐carotene, TBARS and total antioxidative capacity in plasma) (Gessner et al., ). In another study, feeding a polyphenol‐rich plant product consisting of green tea and curcuma extract also did not exert antioxidant effects in dairy cows (Winkler et al., ). Collectively, it can be stated that, like in most studies with monogastric animals, the antioxidant status of dairy cattle is less influenced by supplementation of feed rations with polyphenols from plant sources.…”
Section: Effects Of Polyphenols On Oxidative Stress and Inflammation mentioning
confidence: 99%
“…Conversely, inhibition of the proinflammatory condition during the peripartal phase in dairy cows by early post‐partum treatment with non‐steroidal anti‐inflammatory drugs led to a significant increase in milk yield over the whole lactation period and caused a reduction in somatic cell count in milk being indicative of an improved udder health (Carpenter et al., ). According to these findings, investigations aiming to prevent the proinflammatory condition during the peripartal phase, either by optimization of feeding regimes pre‐partum (Khan et al., ; Zhou et al., ; Vailati‐Riboni et al., ) or by administration of potential antiinflammatory feed supplements (Gessner et al., ,b; Hashemzadeh‐Cigari et al., ; Winkler et al., ), are of great relevance.…”
Section: Consequences Of Inflammation On Performance Of Farm Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Winkler et al (2015), the authors found that the supplementation of cow feed with a combination of 95% green tea and 5% curcumin extract to dairy cows could reduce inflammation and alleviate stressed ER condition in lactating cows. In the study of Winkler et al (2015), the authors found that the supplementation of cow feed with a combination of 95% green tea and 5% curcumin extract to dairy cows could reduce inflammation and alleviate stressed ER condition in lactating cows.…”
Section: Dairymentioning
confidence: 99%
“…S. aureus is the most common cases of mastitis in dairy cows. In Belgium, MRSA isolates obtained from bovine mastitis cases was first reported in the 1970 [39]. EGCG shows antibacterial effects to not only S. aureus but also MRSA.…”
Section: Application Of Catechins For Veterinary Sciencementioning
confidence: 99%